Persisting exercise ventilatory inefficiency in subjects recovering from COVID-19. Longitudinal data analysis 34 months post-discharge - Dorelli, Gianluigi; Sartori, Giulia; Fasoli, Giulia; Ridella, Nicolò; Bianchini, Nicola; Braggio, Michele; Ferrari, Marcello; Venturelli, Massimo; Carbonare, Luca Dalle; Capelli, Carlo; Grassi, Bruno; Crisafulli, Ernesto (BMC pulmonary medicine, 2024)
SARS-CoV-2 infection has raised concerns about long-term health repercussions. Exercise ventilatory inefficiency (EVin) has emerged as a notable long-term sequela, potentially impacting respiratory and cardiovascular health. This study aims to assess the long-term presence of EVin after 34 months and its association with cardiorespiratory health in post-COVID patients. In a longitudinal study on 32 selected post-COVID subjects, we performed two cardiopulmonary exercise tests (CPETs) at 6 months (T0) and 34 months (T1) after hospital discharge. The study sought to explore the long-term persistence of EVin and its correlation with respiratory and cardiovascular responses during exercise. Measurements included also V̇O end-tidal pressure of CO (PET ) levels, oxygen uptake efficiency slope (OUES) and other cardiorespiratory parameters, with statistical significance set at p < 0.05. The presence of EVin at both T0 and T1 defines a persisting EVin (pEVin). Out of the cohort, five subjects (16%) have pEVin at 34 months. Subjects with pEVin, compared to those with ventilatory efficiency (Evef) have lower values of PET throughout exercise, showing hyperventilation. Evef subjects demonstrated selective improvements in DL and oxygen pulse, suggesting a recovery in cardiorespiratory function over time. In contrast, those with pEvin did not exhibit these improvements. Notably, significant correlations were found between hyperventilation (measured by PET ), oxygen pulse and OUES, indicating the potential prognostic value of OUES and Evin in post-COVID follow-ups. The study highlights the clinical importance of long-term follow-up for post-COVID patients, as a significant group exhibit persistent EVin, which correlates with altered and potentially unfavorable cardiovascular responses to exercise. These findings advocate for the continued investigation into the long-term health impacts of COVID-19, especially regarding persistent ventilatory inefficiencies and their implications on patient health outcomes.